THE ANALYSIS OF BRAINSTORMING LEARNING METHOD IMPLEMENTATION IN THE TEACHER PROFESSIONAL ETHICS SUBJECT - Rosdiana, Rosdiana (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to examine the implementation of the brainstorming method in the teacher professional ethics subject at PAI (Islamic Education) Study Program, Faculty of Tarbiyah and Teacher Training, UIN Alauddin Makassar. This research is a qualitative research with pedagogic, sociological, and phenomenological approaches. The data sources of this research consist of primary data and secondary data. The results show that: first, the implementation of the brainstorming learning method is as follows; (a) always creating strong interpersonal, especially empathy, respect and sincerity; (b) creating good relations with students; (c) sincerity in accepting and caring for students; (d) expressions of interest and enthusiasm; and (e) creating an atmosphere of togetherness; second, the results of the brainstorming method gave maximum learning results, such as: (a) intellectual skills, (b) cognitive aspects, (c) affective aspects, and (d) psychomotor aspects or skills. Therefore, the brainstorming method can be an alternative in maximizing student learning outcomes. Abstrak: Tujuan penelitian ini adalah untuk melihat penerapan metode brainstorming Mata Kuliah Etika Pengembangan Profesi Keguruan Prodi PAI Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar, Penelitian ini adalah penelitian kualitatif dengan pendekatan pedagogik, sosiologis, dan fenomenologi. Sumber data penelitian ini terdiri atas data primer dan data sekunder. Hasil penelitian menunjukkan bahwa: Pertama, Analisis Implementasi metode pembelajaran brainstorming pada mahasiswa Prodi PAI Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar sebagai berikut: (a) senantiasa menciptakan interpersonal yang kuat, khususnya empati, respek dan kesungguhan; (b) menciptakan hubungan yang baik dengan mahasiswa; (c) kesungguhan dalam menerima dan peduli terhadap peserta didik atau mahasiswa; (d) mengekspresikan ketertarikan dan antusisme; dan (e) menciptakan suatu atmosfer kebersamaan. Kedua, hasil metode brainstorming pada mahasiswa prodi PAI Fakultas Tarbiyah dan Kegurauan UIN Alauddin Makassar memberikan hasil belajar yang maksimal. Seperti (a) keterampilan intelektual, (b) aspek kognitif, (c) aspek afektif, dan (d) aspek psikomotor atau keterampilan. Oleh karena itu, metode brainstorming dapat menjadi salah satu alternatif dalam memaksimalkan hasil belajar siswa.